2013
DOI: 10.3892/or.2013.2650
|View full text |Cite
|
Sign up to set email alerts
|

ADAM10 is overexpressed in human hepatocellular carcinoma and contributes to the proliferation, invasion and migration of HepG2 cells

Abstract: Abstract.The overexpression of A disintegrin and metalloproteinase 10 (ADAM10) has been found to be closely associated with the development and progression of various types of tumors. However, ADAM10 expression in hepatocellular carcinoma (HCC) and its significance remain largely unknown. The present study aimed to investigate the expression of ADAM10 in human HCC and the effect of ADAM10 gene silencing by siRNA on the proliferation, invasion and migration of HepG2 human hepatoma cells. Immunohistochemistry wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 37 publications
6
21
0
Order By: Relevance
“…Bai et al (22) found that expression of microRNA-122, as a negative regulator of ADAM10, sensitizes HCC cells to sorafenib, a multikinase inhibitor clinically effective against HCC. Yuan et al (23) observed that ADAM10 silencing resulted in inhibition of proliferation and migration as well as HepG2 human hepatoma cell invasion (P<0.05), a finding that is in concordance with the results of the present study. However, Yuan et al (23) did not investigate responses in an in vivo model.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Bai et al (22) found that expression of microRNA-122, as a negative regulator of ADAM10, sensitizes HCC cells to sorafenib, a multikinase inhibitor clinically effective against HCC. Yuan et al (23) observed that ADAM10 silencing resulted in inhibition of proliferation and migration as well as HepG2 human hepatoma cell invasion (P<0.05), a finding that is in concordance with the results of the present study. However, Yuan et al (23) did not investigate responses in an in vivo model.…”
Section: Discussionsupporting
confidence: 93%
“…Yuan et al (23) observed that ADAM10 silencing resulted in inhibition of proliferation and migration as well as HepG2 human hepatoma cell invasion (P<0.05), a finding that is in concordance with the results of the present study. However, Yuan et al (23) did not investigate responses in an in vivo model. The results from the present study revealed that downregulation of ADAM10 expression using the RNA silencing approach in HepG2 tumor cells significantly suppressed cell proliferation, cell migration and cell invasion in vitro, and tumor growth in vivo.…”
Section: Discussionsupporting
confidence: 93%
“…ADAM10 has been shown to be overexpressed in malignant tumors and may be related to the malignant behavior. For instance, overexpression of ADAM10 was detected and to promote cancer cell migration and invasion in non-small cell lung cancer, hepatocellular carcinoma, oral squamous cell carcinoma and bladder cancer (Fu et al, 2014;Guo et al, 2012;Jones et al, 2013;Yuan et al, 2013). Our data are in line with previous reports showing that ADAM10 is correlated with the migration and invasion of tumor cells.…”
Section: Discussionsupporting
confidence: 91%
“…ADAM10 is significantly overexpressed in breast cancer and colorectal cancer (40). Furthermore, ADAM10 has been reported to be secreted from pancreatic cancer cells (41) and is up-regulated in human hepatocellular carcinoma with an additional role in cancer cell migration and malignant transformation (42). In our study, ΑDAM10 displayed a qualitative difference in SiHa and HeLa cell lines and this pattern was actually validated by western blot analysis (Figure 8).…”
Section: Discussionsupporting
confidence: 72%